1996
DOI: 10.1111/j.1600-0420.1996.tb00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Tear film and meibomian gland functions in psoriasis

Abstract: Tear secretion, tear film stability, and meibomian gland function (plugging, volume, and thickness) were assessed in patients with psoriasis vulgaris (n = 70). As compared to that of the healthy controls (n = 125) mean Schirmer I value of psoriatic patients was found to be in normal ranges, whereas tear film break-up time was significantly lowered. When evaluating meibomian gland function, psoriatic patients were found to have higher plugging and thickness indices but a normal volume of meibomian gland secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 10 publications
4
28
0
1
Order By: Relevance
“…18,19 Meibomian gland dysfunction, which is associated with posterior blepharitis, has been proposed to have an increased propensity in patients with psoriasis. 20 Tear film break-up time, a measure of tear film stability/secretion and meibomian gland function, has been found to be lower in patients with psoriasis. [20][21][22] Zengin et al 20 found patients with psoriasis had higher plugging and thickness indices, but normal volumes of meibomian gland secretions.…”
Section: Eyelidsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Meibomian gland dysfunction, which is associated with posterior blepharitis, has been proposed to have an increased propensity in patients with psoriasis. 20 Tear film break-up time, a measure of tear film stability/secretion and meibomian gland function, has been found to be lower in patients with psoriasis. [20][21][22] Zengin et al 20 found patients with psoriasis had higher plugging and thickness indices, but normal volumes of meibomian gland secretions.…”
Section: Eyelidsmentioning
confidence: 99%
“…[20][21][22] Zengin et al 20 found patients with psoriasis had higher plugging and thickness indices, but normal volumes of meibomian gland secretions. The mechanism of this dysfunction in psoriasis is not known, but Zengin et al 20 proposed that increased epithelial turnover leads to high volumes of cell production and subsequent shedding that may ultimately may lead to a mechanical block through the meibomian duct.…”
Section: Eyelidsmentioning
confidence: 99%
“…Jester et al suggested that hyperkeratinization of the duct epithelium causes plugging, resultant dilation of the ducts and disturbance of the secretory function of the glands (Jester et al, 1989). Thus, hyperkeratinization in eyelid margin could affect the structure and function of meibomian glands by plugging the duct and impairing meibum secretion in patients with Psoriasis vulgaris (Zengin et al, 1996). …”
Section: Dermatological Disorders and Meibomian Gland Pathologymentioning
confidence: 99%
“…The tests most commonly used to evaluate tear film changes in clinical practice are tear break-up time, Schirmer 1 test, and corneal and conjunctival staining with fluorescein and Rose Bengal dye [11-13]. The Schirmer1 test is used to measure tear production, and tear film stability is determined by tear film break-up time (TBUT) [14].…”
mentioning
confidence: 99%
“…Tear film and conjunctival changes in this group of patients have also been studied. TBUT has been shown to be decreased, and squamous metaplasia of the conjunctival epithelial cells has been observed [1,11]. …”
mentioning
confidence: 99%